واقع وكالات الانباء في ضوء الاعلام التفاعلي - رزايقية علاء الدين; مقداد شهرزاد; د/ مداني حجاج (جامعة عمار ثليجي الاغواط, 2025)
ملخص باللغة العربية: تهدف هذه الدراسة إلى فهم تأثير الإعلام التفاعلي على واقع وكالات الأنباء في عصر التحول الرقمي، من خلال تحليل التغيرات الجوهرية التي طرأت على بنية وعمليات هذه المؤسسات الإعلامية العريقة. اعتمدت الدراسة المنهج الوصفي التحليلي لاستكشاف كيفية تكيف وكالات الأنباء مع متطلبات البيئة الرقمية التفاعلية، مع التركيز على حالة وكالة الأنباء بالأغواط كنموذج تطبيقي. كشفت النتائج عن تحول جذري في نموذج العمل الإعلامي لوكالات الأنباء، حيث انتقلت من النمط الأحادي التقليدي في نقل الأخبار إلى نموذج تفاعلي متعدد المنصات يشرك الجمهور في عملية الإنتاج والتوزيع الإعلامي. أظهرت الدراسة أن الإعلام التفاعلي أعاد تعريف مفهوم السبق الصحفي، حيث لم تعد السرعة وحدها كافية، بل أصبح التوازن بين السرعة والدقة والتفاعلية هو المعيار الأساسي للتميز الإعلامي. واجهت وكالات الأنباء تحديات متعددة منها كسر احتكار المعلومة، والمنافسة الشديدة من صحافة المواطن، وانتشار المعلومات المضللة، والحاجة لتطوير مهارات مهنية جديدة تتناسب مع البيئة الرقمية. في المقابل، استطاعت هذه الوكالات استثمار الفرص المتاحة من خلال تطوير نموذج متكامل للنشر يجمع بين المنصات التقليدية والرقمية، وتعزيز مكانتها كمصدر موثوق للمعلومات في عصر عدم اليقين الرقمي. خلصت الدراسة إلى أن الإعلام التفاعلي لم يقضِ على دور وكالات الأنباء، بل أعاد تشكيله بطريقة جعلتها أكثر مرونة وتفاعلاً مع احتياجات الجمهور المعاصر. ويرتبط مستقبل هذه الوكالات بقدرتها على التكيف التكنولوجي المستمر مع الحفاظ على القيم الصحفية الأساسية للمصداقية والدقة والمهنية. كلماتمفتاحية:وكالات الأنباء، الإعلام التفاعلي، التحول الرقمي، التكنولوجيا الرقمية، المصداقية الإعلامية، صحافة المواطن، التفاعل الإعلامي، سرعة تداول الأخبار. Abstract: This study aims to understand the impact of interactive media on the reality of news agencies in the era of digital transformation, by analyzing the fundamental changes that have occurred in the structure and operations of these established media institutions. The study adopted a descriptive-analytical approach to explore how news agencies adapt to the requirements of the interactive digital environment, focusing on the case of Al-Oued News Agency as an applied model. The results revealed a radical transformation in the media business model of news agencies, as they transitioned from the traditional unidirectional pattern of news transmission to an interactive multi-platform model that involves the audience in the media production and distribution process. The study showed that interactive media redefined the concept of journalistic scope, where speed alone is no longer sufficient, but the balance between speed, accuracy, and interactivity has become the basic criterion for media excellence. News agencies faced multiple challenges including breaking the monopoly on information, intense competition from citizen journalism, the spread of misinformation, and the need to develop new professional skills suitable for the digital environment. In return, these agencies were able to invest in available opportunities by developing an integrated publishing model that combines traditional and digital platforms andenhances their position as a reliable source of information in an era of digital uncertainty. The study concluded that interactive media did not eliminate the role of news agencies but rather reshaped it in a way that made them more flexible and responsive to the needs of contemporary audiences. The future of these agencies is linked to their ability to continuously adapt technologically while maintaining the fundamental journalistic values of credibility, accuracy, and professionalism. Keywords:News Agencies, Interactive Media, Digital Transformation, Digital Technology, Media Credibility, Citizen Journalism, Media Interaction, News Circulation Speed.